Demographic analysis of the Makkah Province for the purpose of evaluating the balance of the urban system - Derbali, Amani; Farhi, Abdallah (Quaestiones Geographicae, 2022)
Reaching a well-adjusted population distribution is a major challenge for urban settlements. Various research works have been focusing on evaluating the demographic balance of urban systems worldwide. Regularities in population distribution among urban settlements have been noticed and confirmed by empirical studies in the contemporary era. These studies assert that both rank of a city in the demographic hierarchy and its population size are proportionally correlated in a balanced urban system. It has been proved that this correlation is established according to mathematical theories that have been scientifically identified and proved through in-depth research. This article aims to check the conformity of the population distribution of the Makkah Province to two main demographic, organisational theories. In this article, there will be an attempt to measure the variations, evaluate and assess the deviations, interpret the result thereof, and then compare the outcomes of the two methods applied on the Makkah Province.